KETENAGAKERJAAN DALAM ERA EKONOMI DIGITAL STUDI KASUS DI PROVINSI KALIMANTAN TIMUR - Yovita Insan Perwita Utami (BPS Kalimantan Timur, 2022)
The rapidly growing information and communication technology affects economics which known as the digital economy. The digital economy make the economy pattern begin to shift from traditional to modern ways which have an impact on employment in Indonesia. East Kalimantan shares the largest GRDP contribution on the Kalimantan Island and has respectable economic growth in the Information and Communication sector. This study aims to see an overview of labor conditions in the digital economy era in East Kalimantan as no previous study done. The approach used in this study is according to Mesenbourg who divides the digital economy into three main components, namely supporting infrastructure, e-business, and e-commerce. Based on the results of the descriptive analysis, e-business and e-commerce workforce in East Kalimantan has increased. But, digital economy workforce gap between rural and urban areas and a gender gap are still a problem. Most digital economy workers are in the trade sector and have upper secondary education.